A Preferred‐Habitat Model of the Term Structure of Interest Rates - Vayanos, Dimitri; Vila, Jean-Luc (Econometrica, 2021)
This document contains a list of one typo in the main text and six typos in the online appendix of the article. Each typo is followed by an explanation of why it is only a typo and does not affect the analysis in the article. The main text and online appendix refer to the documents in the journal’s website https://www.econometricsociety.org/publications/ econometrica/2021/01/01/preferred-habitat-model-term-structure-interest-rates.